More with worms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Earthworms feed on decaying materials and digest them into humus and other usable forms of nutrients; they also improve soil structure. They are a good source of protein for chicken, fish and pigs. How about rearing earthworms, a science, by the...